ANALISIS PERSYARATAN HIGIENE SANITASI DEPOT AIR MINUM TERHADAP KUALITAS AIR MINUM BERDASARKAN BAKU MUTU LINGKUNGAN DI KOTA JAMBI - Vevi Erika Trisna (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2016)
High demand of drinking water practically make in every residential area in the city of Jambicontained drinking water depot, where people consume drinking water that does not meet environmentalquality standards, it can cause various disorders on health. An effort to prevent the depot must payattention to hygiene and sanitation.The purpose of this study was to determine the condition and the microbiological quality ofdrinking water produced by drinking water depot in the city of Jambi based on environmental qualitystandards in accordance with Permenkes RI no. 492 / Menkes / PER / IV / 2010 sanitation and hygienefactors, factors supervision by the relevant agencies and consumer knowledge of drinking water depot inthe city of Jambi.This type of research is a quantitative research with cross sectional implemented during themonth of October 3 s / d in December 2015 with locations in 8 districts Research and spread over 34villages in the city of Jambi. Examination of microbiological parameters of drinking water conducted inJambi Provincial Health Laboratory. Samples taken as many as 10% of the total population.The results of the 36 samples were examined microbiological quality as much as 13 samples(36.1%) declared ineligible as drinking water.Conclusion The significant relationship between the quality ofthe drinking water produced by drinking water depots based on environmental quality standard s inhygiene and sanitation, aspects of monitoring by relevant agencies and consumer knowledge of drinkingwater depot in the city of Jambi